HSO2+ Formation from Ion‐Molecule Reactions of SO2⋅+ with Water and Methane: Two Fast Reactions with Reverse Temperature‐Dependent Kinetic Trend. Issue 28 (5th April 2017) - Cartoni, Antonella; Catone, Daniele; Bolognesi, Paola; Satta, Mauro; Markus, Pal; Avaldi, Lorenzo
Abstract: In this work an experimental and theoretical study on the formation of HSO2 + ion from the SO2 ⋅+ +CH4 and SO2 ⋅+ +H2 O ion–molecule reactions at different temperatures is reported. Tunable synchrotron radiation was used to produce the SO2 ⋅+ ion in excited ro‐vibrational levels of the ionic ground state X 2 A1 and mass spectrometry was employed to identify the product ions. Calculations in the frame of the density functional theory and variational transition state theory were combined to explore the dynamics of the reactions. The experimental results show that HSO2 + is the only product in both reactions. Its yield decreases monotonically with photon energy in the SO2 ⋅+ +H2 O reaction, while it decreases at first and then increases in the SO2 ⋅+ +CH4 reaction. Theory confirms this trend by calculating the rate constants at different temperatures and explains the results by means of the polar, spin and charge effects as well as structural reorganization occurring in the reaction coordinate. The dynamic behavior observed in these two reactions is of general and fundamental interest. It can also provide some insights on the role of these reactions in astrochemistry as well as in their use as models for bond‐activation reactions. Abstract : Taking charge : The sulfur dioxide radical cation efficiently reacts with water and methane with opposite temperature‐dependent kinetic trend. The experiments with tunable synchrotron radiation show only one product: HSO2 + . Theory explains the results by means of the polar, spin and charge effects as well as structural reorganization occurring along the reaction coordinate.